Mandibular reconstruction using pectoralis major myocutaneous flap in squamous cell carcinoma, clinical case report and literature review - Gallardo Caudillo, Josué (2022)
Squamous cell carcinoma arises from the epithelium of the oral mucosa, common in the fifth and sixth decades of life and is typically associated with risk factors such as smoking and alcohol consumption. Worldwide, the incidence of oral cancer is higher among men than women. The increase in the incidence of cancer in Mexico requires proper management and the use of vascularized flaps to repair defects generated by a hemimandibulectomy with safety margins. Despite the advent of vascularized free tissue grafts, the myocutaneous pectoralis major flap remains a pedunculated flap widely used for the reconstruction of soft tissue defects in the oral and maxillofacial region. The surgical protocol carried out at the ISSSTE “General Ignacio Zaragoza” Regional Hospital for the treatment of mandibular squamous cell carcinoma is shown.